Young street children in Dhaka: perceptions and experiences of 6-8 year old children about life as street children in Dhaka city - Hoque, Jabadul (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2014.